THERMODYNAMIC ASSESSMENT OF THE Pb–Sr SYSTEM - Zhang, Huaqing; Zhang, Cong; Wang, Weiwei; Du, Yong; Zhou, Peng; Hu, Biao; Liu, Zhitao; Wang, Jianchuan; Wang, Jiong (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
The Pb-Sr system has been critically reviewed and modeled by means of the CALPHAD (CALculation of PHAse Diagrams) approach. It contains seven stoichiometric compounds, i.e. SrPb3, Sr3Pb5, Sr2Pb3, SrPb, Sr5Pb4, Sr5Pb3 and Sr2Pb, in which the SrPb3 and Sr2Pb phases melt congruently, and the other five phases form via peritectic reactions. The enthalpies of formation for the intermetallic compounds at 0 K are provided by first-principles calculations. The liquid, fcc and bcc phases are modeled as substitutional solution phases, and the Redlich-Kister polynomials are used to describe their excess Gibbs energies. A set of self-consistent thermodynamic parameters is obtained by considering reliable experimental data and the computed enthalpies of formation. Comprehensive comparisons between the calculated and measured phase diagram and thermodynamic data show that the experimental information is satisfactorily accounted for by the present thermodynamic description.